Por uma teoria da decisão judicial: a discricionariedade decisória e a busca por respostas constitucionalmente adequadas - Tovar, Leonardo Zehuri (2018)
The present work seeks to analyze how judicial cases, in which the judge decides according to his personal convictions, are observed. Firstly, a philosophical survey was made of the most relevant legal schools for the subject, such as the historical one and of the exegesis, as well as of the movement of free law and of the jurisprudence of concepts, interests and values. The problems caused by the various forms of positivism, as well as by the post-positivism and the disorders that the application of such theories can bring to a good judicial foundation were also presented. In subsequential moment, the contributions of authors, such as Gadamer and Lenio Streck, related to hermeneutics were brought forward, especially with regard to the object of work, which is the analysis of decision arbitrariness. At the end, it faced the important contribution that the Brazilian Civil Procedure Code brought to the search of constitutionally adequate responses. This theme was developed following the contributions of philosophical hermeneutics and the necessary change of understanding of important institutes included in the Civil Procedure Code, such as defensive jurisprudence, the rational persuasion, the instrumentality of forms, judicial precedents and their correct application and the principle of proportionality, enabling a paradigm shift capable of overcoming the aforementioned decision arbitrariness.